2014
DOI: 10.1016/j.bbadis.2014.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory roles of c-jun in H5N1 influenza virus replication and host inflammation

Abstract: The cytokine storm which is a great burden on humanity in highly pathogenic influenza virus infections requires activation of multiple signaling pathways. These pathways, such as MAPK and JNK, are important for viral replication and host inflammatory response. Here we examined the roles of JNK downstream molecule c-jun in host inflammatory responses and H5N1 virus replication using a c-jun targeted DNAzyme (Dz13). Transfection of Dz13 significantly reduced H5N1 influenza virus replication in human lung epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 40 publications
2
46
0
Order By: Relevance
“…Many viruses were proved to activate c-Jun transcription factor to promote c-Jun-dependent gene expression and boost virus replication (Holloway and Coulson, 2006;Wei et al, 2009Wei et al, , 2011Xie et al, 2014). In our researches, we found that WSSV infection could enhance both the expression and phosphorylation levels of Lvc-Jun.…”
Section: Discussionmentioning
confidence: 73%
“…Many viruses were proved to activate c-Jun transcription factor to promote c-Jun-dependent gene expression and boost virus replication (Holloway and Coulson, 2006;Wei et al, 2009Wei et al, , 2011Xie et al, 2014). In our researches, we found that WSSV infection could enhance both the expression and phosphorylation levels of Lvc-Jun.…”
Section: Discussionmentioning
confidence: 73%
“…This means that individuals could be protected against the human viruses, but their immune system was not able to react by producing VN antibodies specific to the corresponding new avian virus of H5 subtype. This could be related to the ability of H5 viruses to induce a strong cytokine response after infection (Cheung et al, 2002;Wong and Yeng, 2006;Xie et al, 2014) or it could be the impact of the original antigenic sin (OAS). Kim et al (2009) showed that sequential infection of mice with live viruses caused much more profound original antigenic sin than their infection following immunization with whole inactivated IAV vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Later, mainly proinfl ammatory (particularly IL-6, IL-1, IFN-γ, and TNF-α) but also antiviral (IFN-α/β), as well as other cytokines are produced (e.g. RANTES, MIP-1α/β, MCP-1, MCP-3 and IP-10) (Julkunen et al, 2000;Xie et al, 2014;Zhao et al, 2014;Shen et al, 2015).…”
Section: Discussionmentioning
confidence: 99%